Knowledge, Attitudes, and Behavior of E-Cigarette Users in Indonesia - Masan, Gracekeren Evalasdhy; Raksanagara, Ardini S.; Rinawam, Fedri Ruluwedrata (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Cigarettes, both traditional and electronic, are widely used. In 2018, 9.1% of Indonesians smoked, up from 8.8% in 2016. In several countries, including Indonesia, e-cigarette use has increased. As a result, regulations to minimize the use of e-cigarettes must be implemented. This study aimed to explore the knowledge, attitudes, and behaviors of e-cigarette users in the Indonesian vaper community.Methods: This study was a quantitative study with a cross-sectional method conducted from September to December 2021. Questionnaires were distributed through social media to 42 randomly selected vaper communities. The minimum sample size was 247 respondents. The analysis used was univariate. Results: Of the 247 respondents, most were aged 17–24 years (78%), mostly male (62.7%), 61.5% were high school graduates or equivalent, and 65.2% had a monthly income of less than 3 million rupiah. A total of 53.1% of respondents had good knowledge scores, and 52.6% had a positive attitude toward e-cigarettes. More than half of the respondents were long-time e-cigarette users (57.9%) and dual users (55.9%). E-cigarettes were used irregularly/occasionally (63.6%). The average number of puffs/days was 50–99 puffs/day. As many as 58.7% of respondents wanted to quit smoking.Conclusions: Slightly more than half of the respondents has good knowledge about e-cigarettes, with a positive attitude towards the use of e-cigarettes. Campaign that e-cigarettes are not a substitute for regular cigarettes and awareness regarding the potential dangers of e-cigarettes need to be increased. Government regulations regarding the control of e-cigarettes need to be considered because underage children are already using them.